Gente da noite: cultura popular e sociabilidade noturna em Pelotas, RS (1930-1939) - Carvalho, Thaís de Freitas (2013)
The following study discusses Pelotas's night between 1930 and 1939, with emphasis on night-time sociabilities linked to popular culture in the period. The choice of the 1930s relates to the context of urbanization and modernization of the city, perceived in the analysis of urban development, electrification and promotion of cultural activities. It is evident the relationship of the city and its inhabitants with conceptions and notions of behavior linked to the ideals of modernity and civility, which carried elements of regulation that served the emergence of a capitalism oriented to consumer relations. The confrontation between these new patterns of social interaction and those old values inherited of a rural way-of-life, is considered in this work through the analysis of the night-time sociabilities present in this popular universe. The night-time, chosen by favoring the dominance of employees on their free time, reveals these and other traces of a popular culture that presents itself effervescent and singular, establishing exchanges not only with Brazil - taking into account Vargas's policy prevailing in the period, to bring together all Brazilian states through popular culture - but also with other countries bordering the state of Rio Grande do Sul. Starting from the statements and testimony contained in police investigations and criminal prosecutions of the period, it becomes possible to visualize the vitality of a popular night that wandered through the streets and filled urban space with their meetings, their conflicts and their loves. In order to take some steps to fill this gap in the history of Pelotas, we propose here to discuss the theme "popular night" so that the city of mansions and charqueadas could be also known for its night owls, who, generation to generation, give life to Pelotas's night until today.